2002
DOI: 10.1051/0004-6361:20021077
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on the galaxy luminosity function in the cluster of galaxies Abell 496

Abstract: Abstract.We have derived the galaxy luminosity function (GLF) in the cluster of galaxies Abell 496 from a wide field image in the I band. A single Schechter function reproduces quite well the GLF in the 17 ≤ I AB ≤ 22 (−19.5 ≤ M I ≤ −14.5) magnitude interval, and the power law index of this function is found to be somewhat steeper in the outer regions than in the inner regions. This result agrees with the idea that faint galaxies are more abundant in the outer regions of clusters, while in the denser inner reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
16
2
Order By: Relevance
“…Durret et al (2002) find a slope of −1.79 ± 0.01 in I, whereas we find here a slope of −1.52 ± 0.05. Given our analysis of cosmic variance, we estimate the error from cosmic variance on the slope of Durret et al (2002) to be roughly 0.08. If this error estimate is correct, then the difference in faint-end slopes would be statistically significant.…”
Section: Comparison With Previous Analyses Of Abell 496contrasting
confidence: 95%
See 1 more Smart Citation
“…Durret et al (2002) find a slope of −1.79 ± 0.01 in I, whereas we find here a slope of −1.52 ± 0.05. Given our analysis of cosmic variance, we estimate the error from cosmic variance on the slope of Durret et al (2002) to be roughly 0.08. If this error estimate is correct, then the difference in faint-end slopes would be statistically significant.…”
Section: Comparison With Previous Analyses Of Abell 496contrasting
confidence: 95%
“…This problem has already been highlighted (e.g. Oemler 1974;Durret et al 2002). We improve our analysis by removing those objects whose colour imply that they are background objects.…”
Section: Improvement Using Colour Magnitude Relationsmentioning
confidence: 99%
“…Moreover, we observed that the cluster to cluster variations of the LF found in the literature are due to choice of a fixed metric apertures for all the systems. This is due to the fact that fraction of dwarf galaxies in clusters is an increasing function of the clustercentric distance (see also Durret et al 2002). To keep under control also the possible dependence between the shape of the LF and the cluster mass, we divided our cluster sample (with mass ranges from the statistics and study the average luminosity distribution of the galaxies in each mass bin, we have used the SDSS photometric data to compute a composite luminosity function (LF) by stacking the individual cluster LFs calculated within r 200 .…”
Section: Luminosity Function Shape and Cluster Massmentioning
confidence: 99%
“…In particular, ground-based wide-field instruments like CFHT-12K, AAT-WFI, MPG/ESO-WFI, and INT-WFC are providing large databases for morphological and evolutionary studies of galaxies at low and intermediate redshifts (McMahon et al 2001;Andreon & Cuillandre 2002;Durret et al 2002;Pracy et al 2003;Fasano et al 2003;Hudson et al 2003;Pimbblet & Drinkwater 2004), while highresolution, very deep HST(WFPC2/ACS) observations of distant galaxies are giving us a glimpse at their early evolutionary phases (Blakeslee et al 2004;Ravindranath et al 2004;Thompson 2004;Rix et al 2004;Cimatti et al 2004;Cassata et al 2005). This kind of data is invaluable for the huge information it contains.…”
Section: Introductionmentioning
confidence: 99%